2010
DOI: 10.1109/tste.2010.2044900
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Optimization of Wind Turbine Power Factor Using Stochastic Model of Wind Power

Abstract: This paper proposes a stochastic optimization algorithm that aims to minimize the expectation of the system power losses by controlling wind turbine (WT) power factors. This objective of the optimization is subject to the probability constraints of bus voltage and line current requirements. The optimization algorithm utilizes the stochastic models of wind power generation (WPG) and load demand to take into account their stochastic variation. The stochastic model of WPG is developed on the basis of a limited au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…Gill et al [15] have shown demand curve levelling and studied the problems of locational marginal pricing with the help of DSM and DR programs. Reference [16] has studied the bidding pool-based day-ahead electricity market by using PR and PRDS to manage the congestion management of the transmission network. Some of the research papers have taken bus voltage and line current as random variables by using stochastic optimization (SO) to minimize system losses [17][18].…”
Section: Smart Grids and Demand Side Management With Renewable Energymentioning
confidence: 99%
“…Gill et al [15] have shown demand curve levelling and studied the problems of locational marginal pricing with the help of DSM and DR programs. Reference [16] has studied the bidding pool-based day-ahead electricity market by using PR and PRDS to manage the congestion management of the transmission network. Some of the research papers have taken bus voltage and line current as random variables by using stochastic optimization (SO) to minimize system losses [17][18].…”
Section: Smart Grids and Demand Side Management With Renewable Energymentioning
confidence: 99%
“…Commonly used kernel functions include linear, polynomial, and RBF kernels. An SVM with the following RBF kernel [28] is used for comparison with the proposed WSVM: (4) where is the width of the RBF kernel, which determines the influence area of the SVs over the data space.…”
Section: A Least-square Support Vector Machinementioning
confidence: 99%
“…Several authors have applied stochastic optimization algorithms to wind energy problems in recent literature. Chen et al optimized power factors across a series of wind turbines using sequential quadratic programming, accounting for uncertainty in future wind power generation and other factors. Cheng and Zhang proposed a probabilistic optimization algorithm for the wind turbine dispatch problem in a chance‐constrained formulation, where again wind energy output over a finite horizon is considered as the primary source of uncertainty.…”
Section: Introductionmentioning
confidence: 99%